2014
DOI: 10.1161/hypertensionaha.113.02688
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Urinary Adipsin in Preeclampsia

Abstract: 846P reeclampsia, a devastating pregnancy-specific syndrome complicating 2% to 8% of pregnancies, is responsible for ≈60 000 maternal deaths worldwide every year. It is characterized by new-onset hypertension, proteinuria, and edema and usually develops after 20 weeks of gestation.1,2 Early diagnosis and treatment of preeclampsia is essential for prevention of seizure development and maintaining the fetus in the uterus to mature. Many attempts have been made to meet these purposes. It has been found that alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…In contrast to ET A receptor activation, activation of ET B receptors conveys a vasodilatory response through the production of nitric oxide and cyclooxygenase metabolites. 34 The exact role of endothelin and the relative contributions of the ET A and ET B receptors to preeclampsia are not fully elucidated though recent studies suggest that the system has great potential as a target for the treatment of preeclamspsia. 51,52 …”
Section: Endothelin-1 and Endothelin Type A (Eta) And B (Etb) Receptomentioning
confidence: 99%
“…In contrast to ET A receptor activation, activation of ET B receptors conveys a vasodilatory response through the production of nitric oxide and cyclooxygenase metabolites. 34 The exact role of endothelin and the relative contributions of the ET A and ET B receptors to preeclampsia are not fully elucidated though recent studies suggest that the system has great potential as a target for the treatment of preeclamspsia. 51,52 …”
Section: Endothelin-1 and Endothelin Type A (Eta) And B (Etb) Receptomentioning
confidence: 99%
“…These findings implicate metabolic factors as a potential cause of angiogenic imbalance and further reduced vasorelaxation in obese pregnancies. There are novel adipokine factors including the serine protease adipsin, also known as factor D in the complement system, that are shown to be released to a greater extent from placentas from obese pregnant women (167) and whose levels are found to be greater in the urine from preeclamptic women (167,190). Human studies have also demonstrated reduced levels of placental factors such as sFlt-1 in obese preeclamptic women.…”
Section: Effects Of Obesity On the Release Of Soluble Placental Factorsmentioning
confidence: 99%
“…Three new blood biomarkers [glycosylated fibronectin (GlyFN) [57], transthyretin [58] and vasopressin [59]], and two new urine biomarkers (urine congophilia [60] and urinary adipsin [61]) were identified, which added to our preexisting list of experimental biomarkers (Figure 1). A total of 11 promising single experimental blood and seven urine biomarkers together with the four established markers were ranked according to the following criteria: 1) characteristics related to performance; and 2) other characteristics such as whether a kit or commercial antibodies exist (Table 2A and 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Its concentration remains constant in controls throughout pregnancy in non-PE patients; whereas, its levels start at a higher value in PE patients in the first trimester and increase throughout pregnancy -suggesting that GlyFN could be used as a predictive screening or diagnostic tool [57]. In contrast, urinary adipsin generally has a lower specificity (70%) than GlyFN, but the specificity is 100% when combined with an increased diastolic BP reading [61]. Another interesting and promising candidate is urine congophilia or Congo Red dot test (CRD), which is a rapid, inexpensive, and usable diagnostic method in LRS.…”
Section: Resultsmentioning
confidence: 99%